Androgenic alopecia; the risk–benefit ratio of Finasteride - David L. Rowland; Ion G. Motofei; Ioana Păunică; Petrișor Banu; Mihaela F. Nistor; Stana Păunică; Vlad D. Constantin (Journal of Mind and Medical Sciences)
Finasteride is currently approved and largely used as a therapeutic option for androgenetic alopecia. Apparently a safe drug and effective at the onset, several concerns appeared over time regarding the frequency and magnitude of finasteride adverse effects, which in some cases seem to be even irreversible. This paper presents administration of finasteride in androgenic alopecia from two distinct perspectives. On one hand, androgenic alopecia is a condition that affects especially the self-image and esteem, aspects that are subjective, namely changeable and thus relative. On the other hand, this condition presents a multifactorial etiology, androgens being only in part involved. In addition, androgens have their own physiological roles within the body, so that any androgenic suppression should be carefully advised. Yet, adverse effects induced by Finasteride are only in part documented and treatable. Finally, alternative therapeutic approaches (like topical finasteride) become available, so that the oral administration of Finasteride for androgenic alopecia should be in our opinion reevaluated. As a conclusion, a very detailed and informed discussion should take place with such patients accepting to start a therapy with finasteride for androgenic alopecia.